Re-envisioning education : affirming diversity and advancing justice - Shankar-Brown, Rajni (Emerald Publishing Limited : Information Age Publishing, Inc., 2022)
"With increasing diversity and widening disparities in the United States (National Center for Educational Statistics, 2019; U.S. Census Data, 2018) and globally (Unesco Institute for Statistics, 2019; World Inequality Report, 2018; Pickett, 2018) there are significant challenges and opportunities throughout the educational landscape. Today's educational stakeholders, particulary public school school administrators and teachers, must re-envision education and collectively build equity-centered systems, structures, and practices. Confronting systemic inequality in education can be a daunting task, but it is nonetheless imperative. Connecting theory to practice, this book aims to promote inclusive educational excellence, and will offer valuable insights and inspiration to a wide range of educational stakeholders. Affirming diversity and advancing social justice requires dismantling oppressive customs and structures inside and outside of the classroom, fostering an equitable school culture, building inclusive learning environments, and increasing collective efficacy though best practice. Creating healthier schools and communities requires authentically investing in and supporting historically and socially marginalized students and families. Rooted in social justice and weaving together diverse voices from the field of education, this edited volume will examine equity-focused preK- 12 pedagogical practices and showcase high-impact initiatives. Educators play a vital role in ensuring positive student outcomes and success, but often report feeling inadequately prepared for current challenges (Mitani, 2018; Coalition for Teacher Equality, 2016; Miller, 2013; Jordan, 2012; Papa, 2007). Unfortunately, growing challenges are contributing to turnover rates and shortages (Mordechay & Orfield, 2017; Jacob et al., 2015; Gates et al., 2006) as well as perpetuating social inequities among preK-12 students instead of dismantling them (Beckett, 2018; Rangel, 2018; Manna, 2015; Fuller, 2012). A research study by the National Association of Secondary School Principals (NASSP) and the Learning Policy Institute (LPI) reveals thatpublic schools with higher percentages of low-income students and students of color are more likely to experience administrative and teacher turnover, which compounds equity issues affecting already vulnerable students (Levin and Bradley, 2019). This edited volume will provide educational stakeholders (i.e., school administrators, teachers, service providers, parents/guardians, nonprofit leaders, community members) with a deeper understanding of pedagogical practices that affirm diversity and promote social justice, while offering a current view of educational inequalities juxtaposed with an urgent call to action. School districts across the United States must recognize inequalities and provide increasingly diverse students with needed support and resources, particularly as social dispairties continue to widen and adversely impact millions of students. Through a collection of diverse voices from the field of education (university educators; PreK-12 district leaders, schools administrators and teachers; Nonprofit leaders serving children and youth) this book will illuminate current social inequalities impacting preK-16 students, establish the need to affirm diversity and advance social justice, share practical examples of transformative initiatives including mindful school-family- community partnerships, feature evidence-based pedagogical practices, and provide an array of helpful resources for 21st century educational stakeholders"--